Smartphone-Based Rapid Quantitative Detection Platform with Imprinted Polymer for Pb (II) Detection in Real Samples - de Liss Meza López, Flor; Hernández, Christian Jacinto; Vega-Chacón, Jaime; Tuesta, Juan C.; Picasso, Gino; Khan, Sabir [UNESP]; Sotomayor, María D. P. T. [UNESP]; López, Rosario (MDPI, 2024)
This paper reports the successful development and application of an efficient method for quantifying Pb2+ in aqueous samples using a smartphone-based colorimetric device with an imprinted polymer (IIP). The IIP was synthesized by modifying the previous study; using rhodizonate, 2-acrylamido-2-methylpropane sulfonic acid (AMPS), N,N'-methylenebisacrylamide (MBA), and potassium persulfate (KPS). The polymers were then characterized. An absorption study was performed to determine the optimal conditions for the smartphone-based colorimetric device processing. The device consists of a black box (10 × 10 × 10 cm), which was designed to ensure repeatability of the image acquisition. The methodology involved the use of a smartphone camera to capture images of IIP previously exposed at Pb2+ solutions with various concentrations, and color channel values were calculated (RGB, YMK HSVI). PLS multivariate regression was performed, and the optimum working range (0-10 mg L-1) was determined using seven principal components with a detection limit (LOD) of 0.215 mg L-1 and R2 = 0.998. The applicability of a colorimetric sensor in real samples showed a coefficient of variation (% RSD) of less than 9%, and inductively coupled plasma mass spectrometry (ICP-MS) was applied as the reference method. These results confirmed that the quantitation smartphone-based colorimetric sensor is a suitable analytical tool for reliable on-site Pb2+ monitoring.